(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
Ljubinka Basotova, PhD, professor at the Faculty of Philosophy in Skopje, a renowned classical philologist, pedagogue, scholar, an eminent translator of classical languages, passed away this year, on 18 June 2020. In memory of her fulfilled life and versatile professional career, let us briefly reflect on the contribution and efforts that professor Ljubinka Basotova made for the Macedonian scientific, cultural and education community with her numerous works, research papers, translations, verse translations and textbooks, as well as her scholarly and pedagogical engagement. Even though the focal points in which her exquisite intellectual capacity manifested were mainly in science, translation and teaching, which by their nature, and in case her particularly, are inextricably interlaced in the best way possible, professor Basotova also had erudition and enthusiasm to be committed and successful in other social activities. This sad occasion and tradition call for focusing first on the usual facts of the professor’s professional biography.